(untitled) (Journal of human and social sciences, 2017)
This paper examines the reality of inter-Arab investments from 1980 to 2010, focusing on the factors influencing their flow and mechanisms for facilitation. The study aims to analyze the challenges facing investments among Arab countries, such as political instability, weak infrastructure, and legal and administrative complexities. It also highlights the role of an attractive investment climate in countries like Saudi Arabia and Egypt, and proposes strategies at both the national and regional levels to enhance Arab economic integration and facilitate the movement of capital between Arab states.